Textile electromyography electrodes reveal differences in lower limb muscle activation during loaded squats when comparing fixed and free barbell movement paths - Svensson, Felicia; Aasa, Ulrika; Strong, Andrew (Frontiers in Sports and Active Living, 2022)
Traditional recordings of muscle activation often involve time-consuming application of surface electrodes affixed to the skin in laboratory environments. The development of textile electromyography (EMG) electrodes now allows fast and unobtrusive assessment of muscle activation in ecologically valid environments. In this study, textile EMG shorts were used to assess whether performing squats with the barbell resting freely on the shoulders or using a Smith machine for a fixed barbell movement path is preferable for maximizing lower limb muscle activation. Sixteen athletes performed free and fixed barbell squats in a gym with external loads equivalent to their body mass. Quadriceps, hamstrings and gluteus maximus activation was measured bilaterally with textile EMG electrodes embedded in shorts. Mean quadriceps activation was greater for the free compared with the fixed movement path for the right (mean difference [MD] 14μV, F(1,15) = , Pp = 0.04, ηp2 = 0.28) and left leg (MD 15μV, Pp = 0.01, ηp2 = 0.39) over the entire squat and specifically during the first half of the eccentric phase for the left leg (MD 7μV, Pp = 0.04, d = 0.56), second half of the eccentric phase for both legs (right leg MD 21μV,, Pp = 0.05, d = 0.54; left leg, MD 23μV, Pp = 0.04, d = 0.52) and the first half of the concentric phase for both legs (right leg, MD 24μV, Pp = 0.04, d = 0.56; left leg, MD 15μV, Pp = 0.01, d = 0.72). Greater hamstrings activation for the free path was seen for the second half of the eccentric phase (left leg, MD 4μV, Pp = 0.03, d = 0.58) and first half of the concentric phase (right leg, MD 5μV, Pp = 0.02, d = 0.72). No significant differences were found for gluteus maximus. Textile EMG electrodes embedded in shorts revealed that to maximize thigh muscle activity during loaded squats, a free barbell movement path is preferable to a fixed barbell movement path.